2017
DOI: 10.1016/j.compgeo.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive mechanical model for gas hydrate bearing sediments incorporating inelastic mechanisms

Abstract: Gas hydrate bearing sediments (HBS) are natural soils formed in permafrost and submarine settings where the temperature and pressure conditions are such that gas hydrates are stable. If these conditions shift from the hydrate stability zone, hydrates dissociate and move from the solid to the gas phase. Hydrate dissociation is accompanied by significant changes in sediment structure and strongly affects its mechanical behavior (e.g. sediment stiffenss, strength and dilatancy). The mechanical behavior of HBS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…The set of critical state parameters characterizing the behavior of pure Toyoura sand (ie, hydrate‐free sediment) (Table ) has been calibrated here using the stress‐strain curve and the volumetric response of the host specimen used for the synthetic formation of cementing hydrate ( S h = 0% in Figure C). For the calibration process, values adopted in previous publications that also model the mechanical response of Toyoura sand have been used as a reference . In addition, the different void ratios of 0.6 and 0.75 reported for the cementing and pore‐filling specimens, respectively, have also been considered in the simulations (Table ).…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The set of critical state parameters characterizing the behavior of pure Toyoura sand (ie, hydrate‐free sediment) (Table ) has been calibrated here using the stress‐strain curve and the volumetric response of the host specimen used for the synthetic formation of cementing hydrate ( S h = 0% in Figure C). For the calibration process, values adopted in previous publications that also model the mechanical response of Toyoura sand have been used as a reference . In addition, the different void ratios of 0.6 and 0.75 reported for the cementing and pore‐filling specimens, respectively, have also been considered in the simulations (Table ).…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
“…Previous mechanical models for MHBS that also modeled Masui's et al experimental data assume that the differences in strength and dilatancy observed between cementing and pore‐filling specimens for a given hydrate saturation are controlled by hydrate morphology. However, Masui et al state that if the pore hydrate saturation is the same in both types of specimens (eg, S h ≈ 40% in Figures C and D), shear strength becomes higher for the specimen with lower void ratio.…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
“…Experimental studies have evaluated effects of varying S h (e.g., Masui et al, ; Santamarina & Ruppel, ), temperatures (Jia et al, ; Song et al, ), pore pressures ( u , Jiang, Zhu, et al, ), and effective stresses ( σ 3 ′, Lee, Francisca, et al, ; Miyazaki, Tenma, et al, ) to identify relevant parameters and initial conditions in the geotechnical analysis of GHBS. In particular with the perspective on sand production issues during natural gas production and potential slope failure of fine‐grained sediments, the effects of fines content (Hyodo et al, ; Jung et al, ; Kajiyama, Hyodo, et al, ; Lee, Santamarina, et al, ; Yun et al, ), lithology and consolidation history (Fujii et al, ; Ito et al, ; Santamarina et al, ; Suzuki et al, ; Yoneda et al, ), and thermo‐hydro‐chemo‐mechanical process coupling (Gupta et al, ; Klar et al, ; Sánchez et al, ; Uchida et al, ) have received attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some constitutive models have been proposed to predict the stress‐strain relationship of methane hydrate‐bearing sediments in the recent decade (Lin et al, ; Pinkert et al, ; Sánchez et al, ; Shen et al, ; Uchida et al, ). The simulated strengths of the pore‐filling and cementing types of hydrate‐bearing sediments classified by Dai et al () and Waite et al () were obtained using different values of fitting parameters to interpret the influence of hydrate morphology on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%